The Biological Basis of Mathematical Beauty - Zeki, Semir; Chén, Oliver Y.; Romaya, John Paul (Frontiers in Human Neuroscience, 2018)
Through our past studies of the neurobiology of beauty, we have come to divide aesthetic experiences into two broad categories: biological and artifactual. The aesthetic experience of biological beauty is dictated by inherited brain concepts, which are resistant to change even in spite of extensive experience. The experience of artifactual beauty on the other hand is determined by post-natally acquired concepts, which are modifiable throughout life by exposure to different experiences (Zeki, 2009). Hence, in terms of aesthetic rating, biological beauty (in which we include the experience of beautiful faces or human bodies) is characterized by less variability between individuals belonging to different ethnic origins and cultural backgrounds or the same individual at different times. Artifactual beauty (in which we include the aesthetic experience of human artifacts such as buildings and cars) is characterized by greater variability between individuals belonging to different ethnic and cultural groupings and by the same individual at different times. In this paper, we present results to show that the experience of mathematical beauty (Zeki et al 2014), even though it constitutes an extreme example of beauty that is dependent upon (mathematical) culture and learning, belongs to the biological category and obeys one of its characteristics, namely a lesser variability in terms of the aesthetic ratings given to mathematical formulae experienced as beautiful.